2019
DOI: 10.1016/j.still.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of crop yield responses to application of organic amendments: A critical review

Abstract: In floriculture, plant residues represent 90% of the total solid residues of the production process. It is important to look for alternatives of waste management, in order to be used;An alternative is composting. The objective of this investigation was to evaluate in 4 times with intervals of 11 weeks, the effect of the use of flower compost on some physical, chemical and biological properties of a soil cultivated with sunflower (Helianthus annuus) in greenhouse. The compost three types used: 100% from dianthu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 134 publications
1
60
0
1
Order By: Relevance
“…a), the same rates of key nutrients should be provided by both the unfertilized and fertilized soils (Celestina et al. ). We did not explicitly control for this; however, our data show that SOM may be able to substitute for mineral N fertilizer in some cases depending on the SOM concentration and whether or not the soils were irrigated.…”
Section: Discussionmentioning
confidence: 99%
“…a), the same rates of key nutrients should be provided by both the unfertilized and fertilized soils (Celestina et al. ). We did not explicitly control for this; however, our data show that SOM may be able to substitute for mineral N fertilizer in some cases depending on the SOM concentration and whether or not the soils were irrigated.…”
Section: Discussionmentioning
confidence: 99%
“…The non-significance in maize yields (cob and grain) between organic amendments and DAP in this study may be attributed to the same Nitrogen fertilizer application rate used (50 kg N ha −1 ). Studies have shown that, when organic and inorganic fertilizers are applied at the same rates especially in terms of macronutrients (N, P, and K), similar effects in crop yields are obtained [55][56][57]. Since P and K application rates for the fertilizer treatments differed, no significant differences in maize yields were observed.…”
Section: Cob and Grain Yieldsmentioning
confidence: 99%
“…In these studies, high application rates of organic amendments (>15 t ha −1 ) were used. However, according to Celestina et al [55], although high organic amendment rates will eventually ensure high productivity gains, these gains are not necessarily economical. In addition, these high rates can lead to increased greenhouse gas emissions, higher losses to runoff, and reduced nutrient use efficiency.…”
Section: Cob and Grain Yieldsmentioning
confidence: 99%
“…Within this circular economy paradigm, the reutilization of organic waste and by-products as soil amendments is gaining much interest, since it poses a realistic, cost-effective, and environmentally sound alternative to landfill disposal (the least preferred option for waste management) [22]. Organic amendments, such as composts, animal manures, slurries, crop residues, digestates from the anaerobic treatment of waste, biosolids, etc., are extensively applied to agricultural soil as fertilizers [23,24] or, alternatively, as amendments in soil remediation and reclamation initiatives [25][26][27][28]. Biofertilizers, defined as "mixtures of selected beneficial microorganisms and/or other organic substances (plant growth hormones, vitamins, etc.)…”
Section: Organic Amendmentsmentioning
confidence: 99%